2011
DOI: 10.1111/j.1365-2141.2011.08683.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of immune responses in the pathogenesis of low‐risk MDS and high‐risk MDS: implications for immunotherapy

Abstract: SummaryThe myelodysplastic syndromes (MDS) constitute a group of heterogeneous clonal haemopoietic stem cell disorders, characterized by ineffective and dysplastic haematopoiesis with varying degrees of peripheral cytopenia. Low-risk MDS is characterized by increased apoptosis in the bone marrow (BM) with autoimmune characteristics whereas the advanced or high-risk stages involve immune evasion and secondary DNA damage, giving cells growth potential to progress into acute myeloid leukaemia (AML). Nevertheless,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 177 publications
(186 reference statements)
7
60
0
4
Order By: Relevance
“…1 Recent studies implicate NK cells in the control of myelodysplastic syndromes (MDSs), a heterogeneous spectrum of clonal hematopoietic disorders affecting the myeloid lineage, characterized by cytopenias and transformation to acute myeloid leukemia (AML). 1,2 Whereas higher NK-cell frequencies have been reported in patients with low-risk MDSs, 3 in high-risk cases, NK cells are reduced, with decreased expression of activating receptors and impaired cytotoxicity. 4,5 Each NK cell can express both activating killer immunoglobulinlike receptors (aKIRs) and inhibitory KIRs that interact to regulate NK-effector function.…”
Section: Introductionmentioning
confidence: 99%
“…1 Recent studies implicate NK cells in the control of myelodysplastic syndromes (MDSs), a heterogeneous spectrum of clonal hematopoietic disorders affecting the myeloid lineage, characterized by cytopenias and transformation to acute myeloid leukemia (AML). 1,2 Whereas higher NK-cell frequencies have been reported in patients with low-risk MDSs, 3 in high-risk cases, NK cells are reduced, with decreased expression of activating receptors and impaired cytotoxicity. 4,5 Each NK cell can express both activating killer immunoglobulinlike receptors (aKIRs) and inhibitory KIRs that interact to regulate NK-effector function.…”
Section: Introductionmentioning
confidence: 99%
“…PA is an autoimmune disease in which Th1 CD4 + T lymphocytes reacting to H + /K + -ATPase in the gastric parietal cells play a role in the pathogenesis and patients with PA are at a high risk of complicating other autoimmune diseases [1,2]; however, our literature search did not detect the association between PA and PMR. On the other hand, it is reported that various immunological abnormalities exist in patients with MDS, such as abnormal antigen presentation, reduced T-cell reaction, abnormal B-cell function, abnormal Band T-cell interaction, reduced number and impaired function of natural killer cells, and impaired function of monocytes [7,15,16]. Furthermore, autoimmune diseases are reported to be complicated in about 10% of MDS patients and the association with PMR has been occasionally reported [8,9,11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Several additional immune cell populations such as macrophages and natural killer cells have been shown to increase in number and activity in the marrow of patients with low-risk MDS and to decrease as MDS progresses [49]. While perturbations in the B-cell compartment are less studied, B-cell progenitors may be reduced in low-risk MDS [50].…”
Section: Mds Inflammation and Autoimmunity - Putting The Puzzle Togmentioning
confidence: 99%